CONCEPTUAL METAPHORS OF SPRING IN ENGLISH AND VIETNAMESE SONG LYRICS - Thom, Sy Thi (VNU Journal of Foreign Studies; Vol 37 No 1DO - 10.25073/2525-2445/vnufs.4663, 2021)
This paper summarily reports the results of a study which attempts to identify conceptual metaphors of spring through their representations called metaphorical expressions in English and Vietnamese song lyrics from the cognitive perspective based on the theory of conceptual metaphors initiated by Lakoff and Johnson, with the work Metaphor We Live by (1980a). The data collected from 205 English and Vietnamese songs (98 and 107 songs respectively) from the 20 th century to the present consist of 736 metaphorical expressions. By employing description as the main method with the assistance of comparative method, and utilizing the procedure of conceptual metaphor identification (Steen, 1999, p. 73), the study unveils the similarities and differences of conceptual metaphors of spring in English and Vietnamese songs. The results reveal that English and Vietnamese share 12 conceptual metaphors of spring (out of 20 ones in total). Moreover, the explanations are given to elaborate on these results in terms of culture, including people’s living experiences and environment.